Differential Expression of Several miRNAs and the Host Genes AATK and DNM2 in Leukocytes of Sporadic ALS Patients - Vrabec, Katarina; Boštjančič, Emanuela; Koritnik, Blaž; Leonardis, Lea; Dolenc Grošelj, Leja; Zidar, Janez; Rogelj, Boris; Glavač, Damjan; Ravnik-Glavač, Metka (Frontiers in Molecular Neuroscience, 2018)
Genetic studies have managed to explain many cases of familial amyotrophic lateral sclerosis (ALS) through mutations in several genes. However, the cause of a majority of sporadic cases remains unknown. Recently, epigenetics, especially miRNA studies, show some promising aspects. We aimed to evaluate the differential expression of ten miRNAs, including miR-9, miR-338, miR-638, miR-663a, miR-124a, miR-143, miR-451a, miR-132, miR-206 and let-7b, for which some connection to ALS was shown previously in ALS culture cells, animal models or patients, and in three miRNA host genes, including C1orf61 (miR-9), AATK (miR-338) and DNM2 (miR-638), in leukocyte samples of 84 patients with sporadic ALS. We observed significant aberrant dysregulation across our patient cohort for miR-124a, miR-206, miR-9, let-7b and miR-638. Since we did not use neurological controls we cannot rule out that the revealed differences in expression of investigated miRNAs are specific for ALS. Nevertheless, the group of these five miRNAs is worth of additional research in leukocytes of larger cohorts from different populations in order to verify their potential association to ALS disease. We also detected a significant up-regulation of the AAKT gene and down-regulation of the DNM2 gene, and thus, for the first time, we connected these with sporadic ALS cases. These findings open up new research toward miRNAs as diagnostic biomarkers and epigenetic processes involved in ALS. The detected significant deregulation of AAKT and DNM2 in sporadic ALS also represents an interesting finding. The DNM2 gene was previously found to be mutated in Charcot-Marie-Tooth neuropathy-type CMT2M and centronuclear myopathy (CNM). In addition, as recent studies connected AATK and frontotemporal dementia (FTD) and DNM2 and hereditary spastic paraplegia (HSP), these two genes together with our results genetically connect, at least in part, five diseases, including FTD, HSP, Charcot-Marie-Tooth (type CMT2M), CNM and ALS, thus opening future research toward a better understanding of the cell biology involved in these partly overlapping pathologies.